EMBOLIZATION IN RECURRENT SOFT TISSUE AMELOBLASTOMA EXCISION OF THE MANDIBLE - widodo, agus; Rahmat, Masykur; Rahardjo, Rahardjo; Soetji, Poerwati (Faculty of Dentistry, Universitas Islam Sultan Agung, 2021)
ABSTRACTBackground: Recurrent ameloblastoma can occur after radical treatment, 13.3% up to 19% involves soft tissue. Case of recurrent mandibular ameloblastoma in soft tissue, bleeding is one of the risks that often occurs. One way to reduce intraoperative bleeding is by embolization. Purpose this studi to report the benefits of embolization to reduce intraoperative bleeding in the action of recurrent ameloblastoma in soft tissue.Method: Female patient 32 years old came to RSUP Dr. Sardjito with complaint of lump on her left cheek, with history of post-hemimandibulectomy ameloblastoma 14 years ago. Objective examination of the asymmetrical patient's face with swelling extends to the cheek and pain when pressed, and the size is around 10x10 cm. Embolization using PVA and gelfoam material done before the excision of the tumor to reduce the risk of bleeding. The excision in this case is using lip split method, with bleeding during surgery around 250 ml. Biopsy results after excision are multicystic ameloblastoma, some are follicular types and some are plexiform typesConclusion: The use of embolization in the case of recurrent mandibular ameloblastoma in soft tissue can reduce tumor size and reduce bleeding during surgery.